Therapeutic potential of Cannabis sativa against tick-induced injuries (Rhipicephalus linnaei): biochemical and histopathological evaluation in rabbits - Silva, O. [UNESP]; Sapatini, D. [UNESP]; Rodrigues, M. L. [UNESP]; Evangelista, B. F. [UNESP]; Vicente, B. S. [UNESP]; Marques, A. S. [UNESP]; Leitão, M. L. J. [UNESP]; Lancia, B. C. [UNESP]; Camargo-Mathias, M. I. [UNESP] (FapUNIFESP (SciELO), 2025)
Rhipicephalus linnaei, commonly known as the brown dog tick, are preferential hosts for dogs, to whom they also transmit various pathogens. The control of these ectoparasites is generally achieved through the use of synthetic chemical products, which can lead to the development of resistance. Bioactive compounds extracted from plants are being studied as an alternative strategy for tick control, including Cannabis sativa, which provides an extract from its flowers known for its diverse therapeutic properties, applicable to both humans and animals. Therefore, in the work that originated this project investigated the effects of C. sativa flower extract in oil dilutions of 0.2, 0.4, and 0.8 mg/mL, applied to skin lesions of rabbit hosts of R. linnaei ticks, to evaluate their healing. In addition, this procedure made it necessary to evaluate, what was done in the present work, the hepatic tissue of these animals, as the extract, while functioning as a tickicide and promoting healing of skin lesions, should also be harmless to the hosts to be considered viable for ectoparasite control. For this purpose, histological and histochemical techniques were applied to the livers of the rabbits (to identify morphological alterations), which were divided into: control group (CG), exposed to 1 mL of oil, showing no hepatic alterations; treated group 1 (TG1), exposed to 0.2 mg/mL, showing cytoplasmic vacuolization in hepatocytes; treated group 2 (TG2), exposed to 0.4 mg/mL, displaying intense morphological alterations, including disorganization of hepatocyte cords, hepatocyte hypertrophy, altered nuclei, and signs of cell death; treated group 3 (TG3), exposed to 0.8 mg/mL, also showing tissue disorganization and cellular vacuolization, but to a lesser extent than TG2. In addition to morphological evaluation, the biochemical activity of hepatic enzymes AST and ALT was assessed. An increase in ALT was observed in TG2, while no other groups showed changes in these parameters. Overall, this study concluded that although the C. sativa flower extract at various dilutions has potential as a tickicide and for healing skin lesions (personal communication), it causes hepatic tissue damage in rabbits to varying degrees, with the 0.4 mg/mL dilution showing the highest hepatotoxic potential.